Performance Analysis of Channel Allocation Scheme for A System Model Based On Urban Structure - Kumar, Suyash; Suresh, P.V (International Journal of Computer Sciences and Engineering, 2018)
Frequency channels are scarce resource and available in a limit. Due to this limitation user may experience call termination and call blocking as the traffic increases. We can limit call termination and call blocking by allocating permanent channel to home (apartment) and office user due to very limited movement. They are almost fixed if they communicate with each other frequently and this is the normal scenario in urban areas. By using this strategy these users will not feel any disconnection due to inaccessibility of frequency channel in cell. To achieve this we have proposed a scheme based on fixed channel and analyze the performance for both normal channel allocation and preserved channel allocation for home and office users. We have performed and compared the results of call blocking probability, handover failure probability, call termination due to successful handover probability and probability for not completed calls.